Algoritma Brute Force dalam Sistem Informasi Lowongan Kerja Berbasis Web Di Kota Lhokseumawe - Novia Hasdyna, Ikhlasul Amal (LPPM-UNIKI, 2021)
In looking for job vacancies in the city of Lhokseumawe, applicants usually still use conventional methods, namely byvisiting the company to see the bulletin board, or viewing information from newspapers and other print media. In thisstudy, the author discusses the application of technology to be able to help facilitate job seekers in obtaining informationon job vacancies in the web-based city of Lhokseumawe using brute force algorithm.